2011
DOI: 10.1016/j.yfrne.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol-dependent modulation of auditory processing and selectivity in songbirds

Abstract: The steroid hormone estradiol plays an important role in reproductive development and behavior and modulates a wide array of physiological and cognitive processes. Recently, reports from several research groups have converged to show that estradiol also powerfully modulates sensory processing, specifically, the physiology of central auditory circuits in songbirds. These investigators have discovered that (1) behaviorally-relevant auditory experience rapidly increases estradiol levels in the auditory forebrain;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
100
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 226 publications
(333 reference statements)
12
100
1
Order By: Relevance
“…In turn, hormone levels affect behavioral responses to communication signals in frogs, fish, birds, reptiles and mammals (Adkins-Regen, 2005). In the case of acoustic communication, the reception of signals themselves can be influenced by hormones, as hormones have been shown to increase immediate early gene and electrophysiological responses in the auditory system (Arch and Narins, 2009;Lynch and Wilczynski, 2008;Maney and Pinaud, 2011;Penna et al, 1992;Yoder and Vicario, 2012). Here, we found that the responsiveness of the auditory midbrain to acoustic communication signals can be similarly enhanced by chronic exposure to dynamic conspecific signals.…”
Section: Discussionsupporting
confidence: 51%
“…In turn, hormone levels affect behavioral responses to communication signals in frogs, fish, birds, reptiles and mammals (Adkins-Regen, 2005). In the case of acoustic communication, the reception of signals themselves can be influenced by hormones, as hormones have been shown to increase immediate early gene and electrophysiological responses in the auditory system (Arch and Narins, 2009;Lynch and Wilczynski, 2008;Maney and Pinaud, 2011;Penna et al, 1992;Yoder and Vicario, 2012). Here, we found that the responsiveness of the auditory midbrain to acoustic communication signals can be similarly enhanced by chronic exposure to dynamic conspecific signals.…”
Section: Discussionsupporting
confidence: 51%
“…Our results for the auditory midbrain parallel a number of studies from other taxa that describe an important role for estradiol in sensory processing of social signals and of audition (Arch and Narins, 2009;Caras, 2013;Earp and Maney, 2012;Maney, 2013;Maney et al, 2006Maney et al, , 2008Maney and Pinaud, 2011;Petrulis, 2013;Remage-Healey, 2012, 2014Sanford et al, 2010;Sisneros, 2009c;Tremere et al, 2009;Walpurger et al, 2004;Yovanof and Feng, 1983). In the túngara frog, a previous study showed that hCG, which stimulates production of gonadal steroids (Lynch et al, 2006;Wu et al, 2001), increases egr-1 expression in the laminar nucleus of the torus (Lynch and Wilczynski, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…That is, both reproductive activity (Miranda and Wilczynski, 2009) and estradiol treatment (Yovanof and Feng, 1983) increase auditory responses to sounds in frogs, including biologically irrelevant sounds (noise burst, tones) as well as conspecific calls. There are also broad correspondences between egr-1 (also known as ZENK) expression and electrophysiological activity in songbirds: ZENK expression is selective for conspecific social signals (song) over tones only in the presence of estradiol in female white-throated sparrows (Zonotrichia albicolis) (Maney et al, 2006(Maney et al, , 2008Maney and Pinaud, 2011). Estradiol also enhances auditory encoding of song, sometimes through rapid effects of brain-derived estradiol (Krentzel and Remage-Healey, 2015;Remage-Healey, 2012, 2014RemageHealey et al, 2010;Tremere and Pinaud, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steroid hormones can induce variation in physiological state that dramatically affects responses to socially relevant stimuli (1,36,37). Steroids can also modify cognitive processes ranging from attention (38) to learning (2, 3) that affect the probability and quality of a particular behavioral response.…”
Section: Discussionmentioning
confidence: 99%